2007
DOI: 10.4141/a06-033
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioural responses to short-haul transport by stock trailer in finished steers

Abstract: . 2007. Physiological and behavioural responses to short-haul transport by stock trailer in finished steers. Can. J. Anim. Sci. 87: 291-297. Nineteen British cross-bred steers (623 ± 10.6 kg) were transported in groups of four or five for 3 h and returned to their home pens. Jugular cannulas, heart rate (HR; BPM) monitors and radio transmitters were used to non-invasively collect physiological data. Heart rate (n = 13) was lower during highway travel (83.5 ± 3.15, P > 0.05) compared with pre-loading (118.9 ± 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Several studies suggested that the stress cattle experience as part of the transport process was the result of poor quality handling at loading and unloading rather than the transport itself (Camp et al, 1981;Cole, Camp, Rowe, Stevens, & Hutcheson, 1988). Transport-related handling has been shown to increase plasma cortisol levels and heart rate (Booth-Mclean et al, 2007;Fell & Shutt, 1986) in cattle particularly when handling was rough and involved the use of poorly designed loading facilities (Stermer, Camp, & Stevens, 1982). BoothMclean et al (2007) reported significantly higher heart rates at the time of loading and offloading beef heifers for a 3-h journey compared to heart rates taken during transit.…”
Section: Handling At Loading and Unloadingmentioning
confidence: 97%
“…Several studies suggested that the stress cattle experience as part of the transport process was the result of poor quality handling at loading and unloading rather than the transport itself (Camp et al, 1981;Cole, Camp, Rowe, Stevens, & Hutcheson, 1988). Transport-related handling has been shown to increase plasma cortisol levels and heart rate (Booth-Mclean et al, 2007;Fell & Shutt, 1986) in cattle particularly when handling was rough and involved the use of poorly designed loading facilities (Stermer, Camp, & Stevens, 1982). BoothMclean et al (2007) reported significantly higher heart rates at the time of loading and offloading beef heifers for a 3-h journey compared to heart rates taken during transit.…”
Section: Handling At Loading and Unloadingmentioning
confidence: 97%
“…However, low scores could also be due to cattle being 'stoic' animals, meaning that they do not display evident pain behaviour. Loading and unloading of cattle was hypothesized to be the most stressing events of transportation [34]. Individual gait and attitude assessments were done when animals excited the chute after UN1 and UN2 sampling.…”
Section: Attitude and Gait Scorementioning
confidence: 99%
“…Studies have reported the behavioural and physiological responses of cattle after they have been unloaded from a vehicle into a pen and offered opportunities to eat, drink and rest. Some studies report on the effect of a mid‐journey lairage period before a subsequent journey (Earley et al., 2013; Marti et al., 2017; Meléndez et al., 2020) and others report on post‐transport lairage (Booth‐McLean et al., 2007; Earley et al., 2013; Ross et al., 2016). If cattle are offered feed in a lairage/rest area, the latency to feed might be increased and the amount of feed consumed might be reduced by fear associated with (a) the novelty of their environment, feed and feeding equipment, and (b) unfamiliar animals in the same pen competing for limited access to feed.…”
Section: Assessmentmentioning
confidence: 99%
“…During transport, cattle lay down less than non‐transported controls (Earley et al., 2013). Cattle have been shown to lay down more during the first 3 h after completing a 3‐h journey than they did before the start of the journey (Booth‐McLean et al., 2007). Knowles et al.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation